The effects of metabolic reprogramming during zebrafish tissue regeneration - Borbinha, Jorge Miguel Ramalho (2022)
Regeneration is the ability to fully restore the structure and function of a lost body part, after damage. While mammals have a very limited regenerative capacity, other vertebrates, such as the zebrafish, have the outstanding capacity to fully regenerate organs, like the heart and liver, and appendages, like the caudal fin. The zebrafish caudal fin is a relatively simple tissue. It has a bi-lobed shape that is composed and supported by a series of skeletal elements, called bony-rays. The bony-rays are covered by a monolayer of osteoblasts, the bone-producing cells, and they encompass an inner mesenchymal compartment, containing nerves, blood vessels and fibroblast-like cells. Externally, a multi-layered epidermis covers the bony-rays. The caudal fin possesses a series of advantages that make it an ideal system to study regeneration, namely easy to amputate, quick to regenerate, amenable to live imaging and its amputation does not compromise fish survival. Its amputation triggers a regenerative program that is divided into three steps: first, the wound healing phase, in which the cells from the epidermis migrate to cover the wound site and form a specialized structure called wound epidermis; second, the blastema formation phase, in which mature cells dedifferentiate and migrate distally to form a mass of proliferative cells, called the blastema, the hallmark of fin regeneration; third, the regenerative outgrowth phase, during which there is a series of differentiation and patterning events to restore the lost tissue organization and function. A major focus of our group are the initial stages of regeneration, which are also the most neglected. Early regeneration events include cell fate transition, like dedifferentiation, cell cycle re-entry, and proliferation. Importantly, preliminary results from our lab indicate that early in regeneration, cell dedifferentiation is preceded by a change in the metabolic profile, increasing their preference for glycolysis. Depending on the cellular function and requirements, glucose can have two main destinations: go through the TCA and be oxidised via OXPHOS or be converted into lactate via glycolysis. Switches of the metabolic profile from OXPHOS to glycolysis have already been described in other contexts but only recently proposed to occur in regeneration. Interestingly, lactate, one of the main products of glycolysis, has recently been proposed to be a substrate for lactylation, a newly identified epigenetic modification. Taking this into account, the main goal of this thesis is to unveil the importance of energy metabolism to the regenerative process and explore a potential link between energy metabolism and epigenetics during regeneration through lactylation. Our hypothesis is that after caudal fin amputation there is an early metabolic reprogramming event from OXPHOS to glycolysis that regulates regenerative events such as dedifferentiation and proliferation, partially through modulation of lactylation and epigenetics.We started by investigating whether the caudal fin tissue responded to an amputation by undergoing a metabolic reprogramming. For that, we performed a thorough characterisation of key enzymes and metabolites using transcriptomic and metabolomic approaches. We observed that during the initial regenerative stages, before blastema formation, between 6 and 24 hour-post amputation, there is a dramatic upregulation of several glycolytic and lactate producing enzymes and an increase in the levels of glucose and lactate. This was accompanied by an increase of mitochondrial fission and possibly biogenesis events, which are associated with high glycolysis and cell division. To address the requirement of this increased glycolytic activity for regeneration, we performed functional assays with inhibitors for glycolysis, lactate formation and OXPHOS. Inhibition of glycolysis and lactate production led to a severe and mild impairment of blastema formation, respectively. On the other hand, inhibition of OXPHOS using different compounds had no effect, or slightly accelerated regeneration. Furthermore, inhibition of glycolysis also led to a decrease of cell proliferation and to discrepancies in osteoblast subtypes. Overall, this suggests that a metabolic reprogramming towards glycolysis is critical for the initial set up of the regenerative process that culminates in blastema assembly, contributing, at least, to maintain cell proliferation and for new osteoblast formation and organization. Next, we decided to investigate additional mechanisms by which metabolic reprogramming could be regulating regeneration. Several metabolites generated from glycolysis and OXPHOS contribute for epigenetic modifications. Given the increase in lactate levels and the reduced regenerative capacity when inhibiting lactate production, we proposed that lactate could be necessary to mediate histone lactylation to modulate chromatin dynamics during regeneration. This epigenetic modification has only been recently described, thus lacking proper tools to allow research. Through proteomic analysis, we successfully identified, for the first time, the existence of histone lactylation in the zebrafish. Additionally, we also demonstrated that the levels of histone lactylation increase during the first 24 hours of regeneration, when cells dedifferentiate and begin to proliferate, concomitantly with changes in metabolism. This increase was impaired when glycolysis was inhibited, confirming that lactylation is dependent on the metabolic reprograming towards glycolysis. To identify possible genomic targets of histone lactylation during regeneration, we performed ChIP-sequencing. We observed that histone lactylation was associated with genes related to actin cytoskeleton, axon guidance, electron transport chain, protein phosphorylation and regulation of transcription, among other processes. From these, we further investigated HDAC4, a histone deacetylase that inhibits runx2 expression and regulates osteogenic differentiation. As expected, we observed that the expression levels of hdac4 decreased during the early event of cell dedifferentiation, suggesting that associated histone lactylation could be inhibiting hdac4 expression. Surprisingly, upon glycolysis inhibition during regeneration, which leads to less lactylation, we also detected a further decrease of hdac4 expression. This suggests that the regulation of hdac4 by lactylation is an intricate system that must be thoroughly explored. Comparing the initial stages of caudal fin regeneration with other biological contexts, such as development and cancer, our results highlight some similarities and differences. Like stem cells and growing tumours, we observed that dedifferentiating cells also change their metabolic profile, increasing glycolysis and histone lactylation levels. However, the enhanced activity upon OXPHOS inhibition seems to be specific of the regenerative process. This indicates that studying the differences between these processes is crucial to understand the unique features controlling regeneration. Our observations are in accordance with recent findings describing the requirement of metabolic reprogramming towards glycolysis during zebrafish adult heart and larva tail regeneration, suggesting that the metabolic reprogramming seems to be a shared featured among regenerative processes. Taken together, this project proposes a series of new contributors for the field of tissue regeneration. We demonstrated that a metabolic reprogramming towards glycolysis is critical for the correct progress of caudal fin regeneration and provided for the first-time evidence of the existence of histone lactylation in zebrafish and in regeneration. Future experiments to better understand the mechanism between these two events would greatly improve our understanding of the regenerative process.